Pendampingan Pengelolaan Ibu Hamil dengan Kekurangan Energi Kronik dan Bayi Berisiko Stunting : Assistance in the Management of Pregnant Women with Chronic Energy Deficiency and Babies at Risk of Stunting - Anis Setyowati; Lina Ratnawati; Rizka Mar’atus Sholichah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Pregnant women with Chronic Energy Deficiency and low nutrition knowledge are at risk of pregnancy with anemia. Inhibited fetal growth (IPM) and LBW delivery can increase the risk of stunting. The purpose of this activity was to deal with SEZ problems in pregnant women, babies who are at risk of stunting, and lack of nutrition knowledge. The method used was assistance to pregnant women with Chronic Energy Deficiency until the mother gives birth by providing additional foods high in calories and protein, iron, calcium and folic acid supplementation, as well as education through lectures and discussions. The location was in Puncu District, Kediri Regency with 37 pregnant women with Chronic Energy Deficiency with gestational age of 23-40 weeks. There was an increase in the average weight of pregnant women by 8.9 kg, uterine fundal height increased by an average of 14.06 cm, upper arm circumference increased by an average of 3.9 cm, Hb levels increased by an average of 1.74gr%, Mother's knowledge about nutrition and exclusive breastfeeding increased, breastfeeding skills increased, the baby's weight and upper arm circumference were in the normal category. Assistance for pregnant women with Chronic Energy Deficiency and babies at risk of stunting can improve maternal health during pregnancy and prevent babies from experiencing stunting. ABSTRAK Ibu hamil dengan status gizi KEK dan pengetahuan rendah tentang gizi berisiko terhadap kehamilan dengan anemia. Pertumbuhan janin terhambat (PJT) dan persalinan BBLR dapat meningkatkan risiko stunting pada bayi. Tujuan kegiatan ini adalah menangani masalah KEK pada ibu hamil, bayi yang berisiko stunting, rendahnya pengetahuan tentang gizi. Metode yang digunakan adalah pendampingan kepada ibu hamil KEK sampai ibu melahirkan dan bayinya berusia 3 bulan dengan memberikan makanan tambahan tinggi kalori dan protein, suplementasi tablet tambah darah, kalsium dan asam folat, serta edukasi dengan ceramah dan diskusi. Lokasi di Kecamatan Puncu Kabupaten Kediri dengan 37 ibu hamil KEK dengan usia kehamilan 23-40 minggu. Terdapat peningkatan rerata berat badan ibu hamil sebesar 8,9 kg, tinggi fundus uteri meningkat rata-rata sebesar 14,06 cm, lingkar lengan atas meningkat rata-rata 3,9 cm, kadar Hb meningkat rata-rata sebesar 1,74gr%, pengetahuan ibu tentang gizi dan ASI Eksklusif meningkat, keterampilan menyusui meningkat, berat badan dan lingkar lengan atas bayi dalam kategori normal. Pendampingan ibu hamil KEK dan bayi berisiko stunting dapat meningkatkan kesehatan ibu selama kehamilan dan mencegah bayi mengalami stunting.